2010
DOI: 10.1093/chromsci/48.10.830
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Capillary Electrophoresis Method for Determination of N-Methylpyrrolidine in Cefepime for Injection

Abstract: The present study relates to a new capillary electrophoresis method for the determination of N-methylpyrrolidine, an impurity considered to be toxic and also potential degradation impurity in cefepime hydrochloride drug substance. The newly developed capillary electrophoresis method for determining the content of N-methylpyrrolidine in cefepime for injection has been validated as per International Conference on Harmonization (ICH) guidelines to prove the selectivity, sensitivity, suitability, robustness, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It has been reported that an increase in the NMP level is proportional to the decline in the antibiotic potency of cefepime. 8,9 Monitoring the level of NMP in cefepime is, therefore, important for ensuring drug quality for clinical use and a threshold concentration of NMP in cefepime has been set at 0.3 % (w/w).…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an increase in the NMP level is proportional to the decline in the antibiotic potency of cefepime. 8,9 Monitoring the level of NMP in cefepime is, therefore, important for ensuring drug quality for clinical use and a threshold concentration of NMP in cefepime has been set at 0.3 % (w/w).…”
Section: IImentioning
confidence: 99%
“…At present, there are four main techniques employed for NMP determination: high performance liquid chromatography (HPLC), ion chromatography (IC), capillary electrophoresis (CE) and gas chromatography (GC). 5,6,[8][9][10] There are limitations associated with all these techniques. The HPLC method requires a mobile phase of pH 2 and the IC method uses a column temperature of 40 ˚C; both of these conditions could lead to degradation of cefepime and reduce measurement accuracy.…”
Section: Nmp Cefepimementioning
confidence: 99%
“…Cefepime or its content of N-methyl pyrrolidine were also determined by several methods such as HPLC [12,13], MEKC [14,15], GC [16,17], TLC [18,19], ion chromatography [20,21], spectrophotometry [22,23], spectrofluorimetry [24,25], voltammetry [26], capillary electrophoresis [27,28] and chemilluminescence [29].…”
Section: Introductionmentioning
confidence: 99%
“…Separation of NMP from cefepime has also been accomplished using capillary electrophoresis. [16] However, a significant issue with these techniques is the sample run times, all of these liquid phase techniques require a run time of several minutes to obtain a result. Since cefepime is unstable in solution the more rapidly a sample can be analysed the better, to avoid giving an artificially high level of NMP and 'false positive' results.…”
Section: Introductionmentioning
confidence: 99%